2019
DOI: 10.21608/ejaj.2019.52593
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Saccharomyces cerevisiae and Spirulina platensis on Suppressing Root-knot Nematode, Meloidogyne incognita Infecting Banana Plants under Greenhouse Conditions

Abstract: Banana production is severely hindered by plant-parasitic nematodes (PPNs) worldwide. Chemical nematicide, oxamyl is a systematic compound widely applied for the control of PPNs. Because of increase pests' problems, harmful effects on human and environment caused by chemical pesticides and also increased consumer requirements for safe crops have encouraged research on bio-pesticides production. So, the effect of different stress of the yeast, Saccharomyces cerevisiae and blue green algae (cyanobacteria), Spiru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Soil drench with both S. platensis and S. cerevisiae gave better performance in plant vigor and nematode control providing soybean with various compounds (phytohormones and proteins) which led to an increment in major elements (nitrogen, phosphorous, potassium) and the photosynthetic pigments. This finding was conformed with that of Hamouda et al, (2019) who reported that the usage of S. cerevisiae and S. platensis in combination treatment revealed the greater antagonistic action on M. incognita in potted banana. The presence of flavonoids, polyphenols, phenylalanine, and antioxidants in yeast and cyanobacterium algal extract may affect nematode penetration and reduce gall formation (Chtourou et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Soil drench with both S. platensis and S. cerevisiae gave better performance in plant vigor and nematode control providing soybean with various compounds (phytohormones and proteins) which led to an increment in major elements (nitrogen, phosphorous, potassium) and the photosynthetic pigments. This finding was conformed with that of Hamouda et al, (2019) who reported that the usage of S. cerevisiae and S. platensis in combination treatment revealed the greater antagonistic action on M. incognita in potted banana. The presence of flavonoids, polyphenols, phenylalanine, and antioxidants in yeast and cyanobacterium algal extract may affect nematode penetration and reduce gall formation (Chtourou et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…21, No.2 (2022) Extracts and exudates of cyanobacterium have been reported to inhibit egg hatching and cause immobility and mortality of 2 nd juveniles of plant parasitic nematodes in vitro (Holajjer et al, 2013). Various studies have shown the nematicidal potential of S. platensis against root-knot nematode (Sharma et al, 2007;Shawky et al, 2009;Hamouda et al, 2019;El-Eslamboly et al, 2019). Yeast, Saccharomyces cerevisiae is a promising plant growth promoter for different crops as well as a biocontrol agent of root-knot nematodes (Karajeh 2013;Mokbel and Alharbi 2014;Youssef and El-Nagdi, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By coming into touch with plant roots, cyanobacteria can trigger several nematode defense mechanisms in plants. In order to combat M. incognita, S. platensis increases the catalase activity in the roots of banana plants [106] and stimulates the production of the plant defense compound jasmonic acid in tomato plants [107].…”
Section: The Role Of Cyanobacteria In Controlling Phytopathogensmentioning
confidence: 99%
“…The yeast, S. cerevisiae, reduced infection of M. incognita on Egyptian henbane, Hyoscyamus muticus, and increased its growth (Youssef & Soliman 1997). Hamouda et al (2019) found that S. cerevisiae suppressed the nematode criteria in roots and soil of M. incognita infecting banana roots and also enhanced its growth. Spraying tomato plants with yeast was increased plant growth, chlorophyll in leaf tissues, NPK uptake and increased pod setting as well as total yield, average fruit weight and total solid salts (El-Ghamriny et al, 1999).…”
Section: Introductionmentioning
confidence: 97%